THE USE, QUALITY AND EFFECTIVENESS OF PELVIC EXAMINATION IN PRIMARY CARE FOR THE DETECTION OF GYNAECOLOGICAL CANCER - Hilman, Feisal; Subhakti, M Alvian; Prabowo, Rafik (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Pelvic examinations are vital for timely detection of gynecological cancers in primary care, yet discomfort can deter some women from seeking them. General practitioners face challenges in managing intimacy during exams, impacting their skills and confidence. Understanding these complexities using behavior change models like COM-B can aid in developing interventions to enhance pelvic examination uptake and address barriers in primary care settings for early cancer detection. A systematic review aims to consolidate qualitative studies on GPs' perceptions and experiences regarding pelvic exams, focusing on their role, barriers, and factors influencing GP behavior. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: The search produced 18 results. After looking at the titles and summaries, we found 10 papers that fit our criteria. At first, we excluded several articles because they were written in review style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a cross sectional study, randomized control trial, and several guidelines. Conclusion: Understanding and predicting healthcare provider behavior in gynecological examinations is complex. The Theory of Planned Behavior provided some insights into intentions but didn't fully explain actual behaviors, which were influenced by external factors like workload. Recommendations suggest tailored approaches for high-risk groups and aligning pelvic exams with cervical screening intervals. However, concerns arise from potential overuse of exams and the impact of fee-for-service payments. More comprehensive research is needed to guide noncervical malignancy screenings and comprehend the various factors influencing healthcare provider behavior in these clinical practices.